Prenuptial agreements: Negotiating women's roles and changing how people think love, commitment, and relationships - Kurnia, Ari; Citra, Ajenk Ningga; Mahmudi, Idlan Dzikri; Saragih, Ruth Putryani (Universitas Bunda Mulia, 2025)
The topic of Prenuptial Agreements in Television Series (TV Series) has emerged as a phenomenon reflecting a shift in the societal significance of marriage within popular culture. This study aimed to analyze this concept as a trend in popular culture and negotiation methods for women in Marriage with Benefits, broadcast on Viu, employing a qualitative methodology and utilizing Sara Mills’ Critical Discourse Analysis, which includes subject-object positions and viewer positioning. The findings demonstrated that women are frequently assigned subordinate roles: yet, instances of resistance and negotiation illustrate the fluidity of gender power dynamics. TV Series are a key part of popular culture that changes how people think, act, dress, and talk. In light of Baudrillard's concept of Simulacra, the representation of Prenuptial Agreements appears as a simulation of reality, depicting love and commitment in an exaggerated manner, divorced from its original meanings. This is new because it uses Baudrillard's ideas on Simulacra and Hyperreality to look at how marriage is shown in popular media and how media shape people's views about Prenuptial Agreements through fake andmediated images. In the context of hyperreality, Prenuptial Agreements depicted in television programs go beyond mere fiction: they actively influence societal perceptions of love, commitment, and relationships.